2020
DOI: 10.54386/jam.v22i2.168
|View full text |Cite
|
Sign up to set email alerts
|

Progress and severity of early blight of tomato in relation to weather variables in Jammu province

Abstract: Early blight of tomato caused by Alternaria solani is an economically important disease in all the tomato growing areas worldwide. The effect of weather variables on the per cent disease intensity(PDI) index of early blight were analyzed during the early summer season of five consecutive years from 2013 to 2017. The disease invariably appeared in the 12thStandard Meteorological Week (SMW) and had steep progression throughout the cropping period. Maximum and minimum temperatures had significantly positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In the present studies, different models were generated using MLR out of which the model with the lower AIC value was selected and it was observed that variables like minimum temperature, morning and evening relative humidity and sunshine hours resulted in ~92%–95% and 97%–99% variation for PDI in all the varieties during 2019 and 2020, respectively. Prediction of disease in different crops using step wise regression analysis was reported by various workers (Biswas et al, 2011; Gupta et al, 2017, 2020). All the assumptions related to the developed model were acceptable in all the test varieties during both the years.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the present studies, different models were generated using MLR out of which the model with the lower AIC value was selected and it was observed that variables like minimum temperature, morning and evening relative humidity and sunshine hours resulted in ~92%–95% and 97%–99% variation for PDI in all the varieties during 2019 and 2020, respectively. Prediction of disease in different crops using step wise regression analysis was reported by various workers (Biswas et al, 2011; Gupta et al, 2017, 2020). All the assumptions related to the developed model were acceptable in all the test varieties during both the years.…”
Section: Discussionmentioning
confidence: 92%
“…selected and it was observed that variables like minimum temperature, morning and evening relative humidity and sunshine hours resulted in ~92%-95% and 97%-99% variation for PDI in all the varieties during 2019 and 2020, respectively. Prediction of disease in different crops using step wise regression analysis was reported by various workers (Biswas et al, 2011;Gupta et al, 2017Gupta et al, , 2020. the lesser the RMSE value, the better a model is able to fit in a given dataset.…”
Section: Assumptions Of Mlr For Sheath Rot Of Ricementioning
confidence: 98%
“…Singh et al [8] concluded that temperature (maximum and minimum) had a significant positive correlation with disease intensity whereas relative humidity (morning and evening) was negatively correlated with tomato early blight intensity in Haryana. Gupta et al [9] reported maximum and minimum relative humidity along with rainfall had a significantly negative correlation with the disease intensity of early blight of tomato in Jammu. Early blight on lower leaves may be more severe than on upper leaves because the environment is most highly favorable within the crop canopy.…”
Section: Correlation Studiesmentioning
confidence: 97%